Assay of steroids by liquid chromatography–tandem mass spectrometry in monitoring 21-hydroxylase deficiency - Dahl, Sandra R (Endocr Connect, 2018)
Immunoassays of steroid hormones are still used in the diagnosis and monitoring of patients with congenital adrenal hyperplasia. However, cross-reactivity between steroids can give rise to falsely elevated steroid levels. Here, we compare the use of immunoassays and liquid chromatography–tandem mass spectrometry (LC–MS/MS) in the monitoring of patients with classic 21-hydroxylase deficiency (21OHD). Steroid profiles in different mutation groups (genotypes) were also compared. Fifty-five patients with classic 21OHD (38 women) were studied. Blood samples were collected in the morning after an overnight medication fast. LC–MS/MS and immunoassays were employed to assay 17-hydroxyprogesterone (17OHP), testosterone and androstenedione. In addition, 21-deoxycortisol (21DF), 11-deoxycortisol (11DF), corticosterone, deoxycorticosterone, cortisone and cortisol were analyzed by LC–MS/MS. Testosterone, androstenedione and 17OHP levels were consistently lower (by about 30–50%) when measured by LC–MS/MS compared with immunoassays, with exception of testosterone in men. There was a significant correlation between 21DF and 17OHP (r = 0.87, P < 0.001), but three patients had undetectable 21DF. Subjects with no enzyme activity had significantly lower mean 11DF concentrations than subjects with residual activity. The use of LC–MS/MS gives a more specific view of adrenal steroid levels in 21OHD compared with immunoassays, which seem to considerably overestimate the levels of 17OHP and androstenedione. Falsely elevated levels of 17OHP and androstenedione could lead to overtreatment with glucocorticoids.